Kisspeptin-54 triggers egg maturation in women undergoing in vitro fertilization - Jayasena,CN; Abbara,A; Comninos,AN; Nijher,GMK; Christopoulos,G; Narayanaswamy,S; Izzi-Engbeaya,C; Sridharan,M; Mason,AJ; Warwick,J; Ashby,D; Ghatei,MA; et al. (Journal of Clinical Investigation, 2014)
BACKGROUND. Patients with mutations that inactivate kisspeptin signaling are infertile. Kisspeptin-54, the major circulating isoform of kisspeptin in humans, potently stimulates reproductive hormone secretion in humans. Animal studies suggest that kisspeptin is involved in generation of the luteinizing hormone surge, which is required for ovulation; therefore, we hypothesized that kisspeptin-54 could be used to trigger egg maturation in women undergoing in vitro fertilization therapy.METHODS. Following superovulation with recombinant follicle-stimulating hormone and administration of gonadotropin-releasing hormone antagonist to prevent premature ovulation, 53 women were administered a single subcutaneous injection of kisspeptin-54 (1.6 nmol/kg, n = 2; 3.2 nmol/kg, n = 3; 6.4 nmol/kg, n = 24; 12.8 nmol/kg, n = 24) to induce a luteinizing hormone surge and egg maturation. Eggs were retrieved transvaginally 36 hours after kisspeptin injection, assessed for maturation (primary outcome), and fertilized by intracytoplasmic sperm injection with subsequent transfer of one or two embryos.RESULTS. Egg maturation was observed in response to each tested dose of kisspeptin-54, and the mean number of mature eggs per patient generally increased in a dose-dependent manner. Fertilization of eggs and transfer of embryos to the uterus occurred in 92% (49/53) of kisspeptin-54–treated patients. Biochemical and clinical pregnancy rates were 40% (21/53) and 23% (12/53), respectively.CONCLUSION. This study demonstrates that a single injection of kisspeptin-54 can induce egg maturation in women with subfertility undergoing in vitro fertilization therapy. Subsequent fertilization of eggs matured following kisspeptin-54 administration and transfer of resulting embryos can lead to successful human pregnancy.TRIAL REGISTRATION. ClinicalTrials.gov NCT01667406.FUNDING. Medical Research Council, Wellcome Trust, and National Institute for Health Research.